Perceived oral health and oral health behaviours among home-dwelling older people with and without domiciliary care - Salmi Riikka; Närhi Timo; Suominen Auli; Suominen Anna Liisa; Lahti Satu (Wiley, 2022)
Objectives
The aim was to compare the perceived oral health and oral health behaviours of home-dwelling older people with and without domiciliary care.
Background
Oral health is poor in long-term care, but less is known about perceived oral health of home-dwelling older people receiving domiciliary care.
Materials and methods
Data from the Health 2000 and Health 2011 surveys (BRIF8901) were used. Interview participants were at least 70 years old and living at home with or without domiciliary care (n = 1298 in 2000 and n = 1027 in 2011). Differences in perceived oral health (subjective oral health, pain, eating difficulties) and oral health behaviours (hygiene, use of services) were compared based on the use of domiciliary care and stratified by gender. Differences between groups were compared with the chi-square test.
Results
In 2011, compared to non-clients, domiciliary care clients more often had poor subjective oral health (40.3% vs. 28.9%, P = .045). In both surveys, they also used oral health services less recently (2000, 76.4% vs. 60.9%; and 2011, 61.1% vs. 46.6%) and more often had difficulties chewing hard food (2000, 50.6% vs. 34%, P < .001; and 2011, 38.4% vs. 20.7%, P < .001) than non-clients. In 2000, clients had more difficulty eating dry food without drinking (39.5% vs. 21.6%, P < .001) and cleaning their teeth and mouth (14.3% vs. 1.1%, P < .001) than non-clients. Women clients in 2011 brushed their teeth less often than non-clients (43.5% vs. 23.7%, respectively, P = .001).
Conclusion
Domiciliary care clients have poorer perceived oral health, and greater difficulties with eating and oral hygiene maintenance than non-clients.